Risk Factors and Outcome of Complicated Typhoid Fever at Dr M R Khan Shishu Hospital - Abiduzzaman, MF; Ghosh, Uzzal Kumar; Afroze, Sharmin; Rahat, Farhana; Choudhury, Ahmed Murtaza (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Typhoid fever is caused by salmonella typhi which invades the bloodstream causes systemic involvement & different complications. This study was designed to evaluate the complications of typhoid fever in children admitted to a tertiary care hospital. Methodology: This retrospective cross-sectional study was conducted at Dr. M R Khan Shishu Hospital & ICH, over twelve months from July 2019 to June 2020 of 100 children aged 6 months to 15 years who were diagnosed with typhoid fever. Complete history, physical examination and investigation were done to reach the complications. Complications were evaluated and data were analyzed. Results: Complications were found in 37% of typhoid fever cases. Among them, hepatitis, UTI, pneumonia, thrombocytopenia were mostly observed. The majority were boys from poor socio-economic Backgrounds. Complications were usually found on the third week and significantly associated with male child, young age, poor socio-economic Background, poor oral compliance, delay treatment, leukocytosis and thrombocytopenia. Conclusion: A significant portion of children with typhoid fever can develop complications. J Bangladesh Coll Phys Surg 2023; 41: 58-62